2004
DOI: 10.1080/09546630310013379
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus foliaceus: an adverse reaction to lisinopril

Abstract: Lisinopril is an angiotensin converting enzyme inhibitor used in the treatment of cardiovascular disease. We report a case of pemphigus foliaceus in a 66-year-old male treated with lisinopril for hypertension and a previous myocardial infarction. The drug-induced variant of pemphigus is caused by a wide variety of drugs and is most frequently associated with captopril and penicillamine. It has not previously been reported in this commonly used drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Thus, given the temporal association between the patient's isolated Lisinopril dose escalation and her skin eruptions 2 months later, a drug‐induced adverse reaction was entertained. Particularly, drug‐induced pemphigus foliaceus (PF), another autoimmune blistering skin disorder, was highly suspected, given its previous reporting twice within the literature in association with Lisinopril use , along with the flaccid, eroded and crusted nature of our patient's skin lesions and their mucous‐sparing distribution .…”
Section: Case Presentationmentioning
confidence: 89%
“…Thus, given the temporal association between the patient's isolated Lisinopril dose escalation and her skin eruptions 2 months later, a drug‐induced adverse reaction was entertained. Particularly, drug‐induced pemphigus foliaceus (PF), another autoimmune blistering skin disorder, was highly suspected, given its previous reporting twice within the literature in association with Lisinopril use , along with the flaccid, eroded and crusted nature of our patient's skin lesions and their mucous‐sparing distribution .…”
Section: Case Presentationmentioning
confidence: 89%
“…To our knowledge, this is the first observational study investigating the influence of ACE inhibitor and ARB use and incident RA. Evidence for the association between ACE inhibitor and/or ARB use and the occurrence of autoimmune diseases was derived from case reports of lupus‐like disease, vasculitis, and pemphigus . In these case reports, the commonly prescribed ACE inhibitors such as captopril and enalapril were often reported as a suspected drug for the occurrence of these autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, it has been postulated that the immunomodulating effects of ACE inhibitors may facilitate autoimmune responses . Indeed, several case reports have suggested that ACE inhibitors may facilitate the development of autoantibodies and autoimmune diseases such as lupus‐like syndrome, vasculitis, and pemphigus . Furthermore, one patient with ARB‐associated pemphigus has been reported …”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that pemphigus foliaceus might be induced by lisinopril. 6 To our knowledge, we are presenting the first patient in whom BP developed during treatment with lisinopril-another ACE inhibitor lacking the thiol group ( Fig. 1).…”
mentioning
confidence: 93%
“…These drugs are used for the treatment of arterial hypertension, either as a monotherapy or in combination with other drugs, and in congestive heart failure. It was recently shown that pemphigus foliaceus might be induced by lisinopril 6 . To our knowledge, we are presenting the first patient in whom BP developed during treatment with lisinopril—another ACE inhibitor lacking the thiol group (Fig.…”
mentioning
confidence: 97%